Obstacles to emergency medical consultation in cases of conflict-related sexual violence - Denis Mukwege; Gilbert M. Mugisho; Raha Maroyi (PLoS ONE, 2025)
Background Despite the availability of a well-developed holistic care model for victims of conflict-related sexual violence, little is known about the factors that determine late presentation for care post-sexual violence care. Drawing from data from the Democratic Republic of the Congo, this study aimed to determine obstacles to accessing emergency medical care within 72-hours of sexual violence (SV). Methods We retrospectively analyzed data from 4048 victims of SV treated at Panzi Hospital (PH) in Bukavu city between 2015 and 2018. The factors of access to care within 72h were analyzed using logistic regression. Results 88% of the victims consulted after 72h post sexual violence. Several sociodemographic factors were found to limit access to the medical care post-sexual violence including the victim’s age (p = 0,022), place of residence (p = 0,000) and education level (p = 0,039). Clinical discomfort from pain during urination (p = 0,002) and fear of pregnancy (p = 0,000) were also associated with late assessment of care. Conclusion Seeking medical care within 72 hours after sexual violence within the critical 72-hours timeframe is crucial to avoid several medical complications stemming from SV. Improvement will be achieved by integrating the post-exposure prophylaxis protocol into primary health care, as well as by increasing community awareness of the relevance of timely consultation after sexual abuse.